Pemanfaatan Minyak Jelantah Sebagai Lilin Aromaterapi Dalam Rangka Mengatasi Ketidaksetabilan Ekonomi - Apri Kuntariningsih; Samtono Samtono; Tri Maryani (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2024)
One of the training programs that can increase economic income is making Aromatherapy candles, namely by utilizing used cooking oil waste, taking into account that the available resources are easy to obtain and also ingredients that can be used every day. The aim of this community service is to empower young housewives, young men and women and students around residential areas to produce Aromatherapy candle products from used cooking oil and increase community knowledge about how to make Aromatherapy candles using environmentally friendly raw materials. The method of implementing this training is a direct demonstration of aromatherapy candle making techniques using prepared materials and how to make them. The results of the training show the potential for significant social change, both in material (candle production) and non-material (change in mindset) aspects. Changes in participants' mindsets about waste and entrepreneurship reflect a transformative learning process.